Understanding Female Gamers’ Experiences in Online Video Games Communities - KHADIJAH, MOHAMAD TUAH; AHMED SHAMSUL BAHRI, MOHAMAD TUAH; ROZRINA, HASBI (Universiti Kebangsaan Malaysia, 2025)
Gaming culture has evolved significantly, transitioning from localized arcades to global digital platforms that connect diverse players. This study explores the lived experiences of female gamers, focusing on the intersection of gender and technology in online gaming spaces. It aims to examine the systemic barriers female gamers face, such as discrimination, gender-based stereotypes, and harassment, while also identifying the coping strategies they employ to navigate these challenges. Objectives of study include exploring discriminatory practices and gender stereotypes female gamers encounter in online video game communities, investigating the effects of gender preconceptions on female gamers' experiences and interactions in online gaming communities, and analysing how female gamers negotiate their identities within online video game communities. Social Identity Theory is used as it is relevant in gaming, where identity is constructed through participation in virtual communities. Eight female gamers were interviewed and the results were analysed thematically. Findings are divided into discriminatory practices and gender stereotypes faced by female gamers, the effects of gender preconceptions on female gamers’ experiences and how female gamers negotiate their identities in online gaming communities. Participants described balancing their identities by selectively engaging with different aspects of gaming culture. Despite encountering challenges, female gamers demonstrate resilience, actively challenging stereotypes, and foster supportive networks to counteract the toxicity they face.